Brain Endothelial Cells Synthesize Neurotoxic Thrombin in Alzheimer’s Disease - Yin, Xiangling (American Society for Investigative Pathology, 2010)
Alzheimer’s disease (AD) is characterized by neuronal death; thus, identifying neurotoxic proteins and their source is central to understanding and treating AD. The multifunctional protease thrombin is neurotoxic and found in AD senile plaques. The objective of this study was to determine whether brain endothelial cells can synthesize thrombin and thus be a source of this neurotoxin in AD brains. Microvessels were isolated from AD patient brains and from age-matched controls. Reverse transcription-PCR demonstrated that thrombin message was highly expressed in microvessels from AD brains but was not detectable in control vessels. Similarly, Western blot analysis of microvessels showed that the thrombin protein was highly expressed in AD- but not control-derived microvessels. In addition, high levels of thrombin were detected in cerebrospinal fluid obtained from AD but not control patients, and sections from AD brains showed reactivity to thrombin antibody in blood vessel walls but not in vessels from controls. Finally, we examined the ability of brain endothelial cells in culture to synthesize thrombin and showed that oxidative stress or cell signaling perturbations led to increased expression of thrombin mRNA in these cells. The results demonstrate, for the first time, that brain endothelial cells can synthesize thrombin, and suggest that novel therapeutics targeting vascular stabilization that prevent or decrease release of thrombin could prove useful in treating this neurodegenerative disease.